(untitled) (Research, Society and Development, 2022)
Introduction: Mental disorders encompass a set of psychiatric dysfunctions with negative repercussions on the biological body. In this context, studies suggest that women present twice the risk of depressive disorders when compared to men. Objective: To conduct a literature review in order to assess the association between the use of hormonal contraceptives and the development of mental health disorders. Methodology: Integrative literature review on the PubMed database of productions from the last 12 years. The descriptors used were: "Hormonal Contraceptive", "Psychiatric Disorder", "Mental Health" and "Women’s Health", which were combined to delimit the search. Result: Seven articles were selected at the end of the search steps. The year 2016 was the most prevalent with 28.57% of the publications. Regarding the country of origin of the studies, 42.85% were conducted in the United States of America. It was found, from the Integrative Review, that the use of hormonal contraceptives attenuates symptoms of the menstrual cycle, such as anger and irritability. However, worsening of depression-related symptoms, and reduced sexual desire, arousal, and pleasure have also been reported. It is also seen that the combination with antidepressants may not be effective in treating premenstrual depression. There is also an association of worsening mood in women with a history of mood, anxiety and eating disorders. Conclusion: mental state changes were evidenced with the use of hormonal contraceptives, with emphasis on the worsening of depressive symptoms, sexual pleasure and anxiety, especially in those patients with a previous history of mood disorders.